Detection of hydrogen peroxide in Photosystem II (PSII) using catalytic amperometric biosensor - Prasad, Ankush; Kumar, Aditya; Suzuki, Makoto; Kikuchi, Hiroyuki; Sugai, Tomoya; Kobayashi, Masaki; Pospíšil, Pavel; Tada, Mika; Kasai, Shigenobu (Frontiers in Plant Science, 2015)
Hydrogen peroxide (H2O2) is known to be generated in Photosystem II (PSII) via enzymatic and non-enzymatic pathways. Hydrogen peroxide (H2O2) is known to be generated in Photosystem II (PSII) via enzymatic and non-enzymatic pathways. Detection of H2O2 by different spectroscopic techniques has been explored, however its sensitive detection has always been a challenge in photosynthetic research. During the recent past, fluorescence probes such as Amplex Red has been used but is known to either lack specificity or limitation with respect to the minimum detection limit of H2O2. We have employed an electrochemical biosensor for real time monitoring of H2O2 generation at the level of sub-cellular organelles. The electrochemical biosensor comprises of counter electrode and working electrodes. The counter electrode is a platinum plate, while the working electrode is a mediator based catalytic amperometric biosensor device developed by the coating of a carbon electrode with osmium-horseradish peroxidase which acts as H2O2 detection sensor. In the current study, generation and kinetic behaviour of H2O2 in PSII membranes have been studied under light illumination. Electrochemical detection of H2O2 using the catalytic amperometric biosensor device is claimed to serve as a promising technique for detection of H2O2 in photosynthetic cells and subcellular structures including PSII or thylakoid membranes. It can also provide a precise information on qualitative determination of H2O2 and thus can be widely used in photosynthetic research.